2010
DOI: 10.21273/hortsci.45.10.1516
|View full text |Cite
|
Sign up to set email alerts
|

Plant Performance and Nutrient Losses during Containerized Bedding Plant Production Using Composted Dairy Manure Solids as a Peat Substitute in Substrate

Abstract: Recent concerns over the environmental impact of peat harvesting have led to restrictions on the production of peat in Florida and other areas. The objectives of this study were to evaluate the use of composted dairy manure solids as a substitute for sphagnum or reed-sedge peat in container substrates on the growth of Solenostemon scutellarioides L. Codd ‘Wizard Velvet’, Tagetes patula L. ‘Safari Queen’, and Begonia × Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Some studies recently evaluated the use of composted residues (urban solid waste, sewage sludge, livestock manure and agroindustrial waste) or solid fraction of digestates (coming from biogas plants) as alternatives to peat (Bustamante et al, 2008;De Lucia et al, 2013;Moldes et al, 2007;Ostos et al, 2008;Ronga et al, 2016Ronga et al, , 2018aShober et al, 2010;Tittarelli et al, 2009). In general, all authors suggested that a partial replacement of commercial peat with up to 20% of compost alternatives is an approach that could improve agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies recently evaluated the use of composted residues (urban solid waste, sewage sludge, livestock manure and agroindustrial waste) or solid fraction of digestates (coming from biogas plants) as alternatives to peat (Bustamante et al, 2008;De Lucia et al, 2013;Moldes et al, 2007;Ostos et al, 2008;Ronga et al, 2016Ronga et al, , 2018aShober et al, 2010;Tittarelli et al, 2009). In general, all authors suggested that a partial replacement of commercial peat with up to 20% of compost alternatives is an approach that could improve agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Mean growth parameter measures for herbacious nursery crops grown in grown in bark-peat-perlite and bark-ADDF-perlite mixes. Significant differences ( * ) at P ≤ 0.05. dairy manure and dissolve at pH below 7 [21]. The continued release of N throughout the trial suggests the mineralization of organic N into plant available forms.…”
Section: Resultsmentioning
confidence: 98%
“…Li et al [62] concluded that there was potential to use cowpeat in foliage plant propagation and for foliage plant production. Shober et al [63,64]) used cowpeat obtained from the same source at about the same time as [62] as a peat substitute in substrates for the container production of three annual bedding plants and three woody landscape shrubs. Their results indicated substrates formulated with cowpeat appeared to be commercially acceptable for production of container-grown bedding plant and woody landscape shrub species based on growth and quality [63].…”
Section: Ad Fiber As a Component Of Growth Substrates Used In Containmentioning
confidence: 99%